La defensa de la legalidad y de las instituciones: Antonio de los Ríos Rosas - Martínez-sicluna y Sepúlveda, Consuelo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2007)
This paper deals with the study of Ríos Rosas’ work. He was one the key figures during the process of the nineteenth-century Spanish parliamentarianism and also played a prior role in a period of time in which was consolidated the constitutional system of the Spanish political life in accordance with the principles of legitimacy, obedience to the rule of law, defense of public institutions and modernisation of the Administration.